DYNAMICS OF ALTERNATIVE EDUCATION FOR REFUGEES: A CASE STUDY OF THE SCHOOL FOR REFUGEE PROGRAM - Yulianti, Yulianti; Kharima, Nadya; Haryadi, Pedri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The right to education is one of the fundamental human rights, irrespective of one's status. Therefore, the right to education should also be available to refugees. The education rights of refugees are protected under the 1951 Refugee Convention, where the contracting states must provide basic education. However, not all countries have joined this convention, including Indonesia, which has not ratified the 1951 Geneva Convention and the 1967 Protocol on the Status of Refugees. Although the Indonesian government has not been able to fulfill these obligations, there are civil society organizations providing alternative education to help refugees sustain themselves in Indonesia until they have the opportunity for resettlement. One such organization is Dompet Dhuafa with its School for Refugee (SFR) program, which aims to provide alternative education for refugee children. This research aims to analyze the needs of refugees in preparing for the resettlement stage. The method used in the research is qualitative, where data collection is carried out directly with involved stakeholders, as well as documentation and literature obtained from primary sources. The conclusion of this research is that there are several requirements that refugees must meet in the resettlement process, including proficiency in English, soft skills, and hard skills. Additionally, in the implementation of the program, the SFR team found that the preparation for the Indonesian language is not only for children but also for adult refugees. Hence, there is a need to establish a Learning Empowerment Center for refugees with the hope that they can meet the requirements for the resettlement process.